2010
DOI: 10.2174/1874336600902010008
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Variation Among Aquatic Gastropod Assemblages of Indiana, USA~!2008-11-19~!2008-12-24~!2009-01-22~!

Abstract: We collected aquatic gastropods at 137 sites in lakes and streams of Indiana and tested for patterns of assemblages with environmental variables. The survey resulted in 32 species with a mean of 2.8 species at each site, and a mean abundance at each site of 144 individuals. Nonmetric multidimensional scaling (NMS) multivariate analyses resulted in watershed drainage area, water conductivity, substrate category frequency, and dissolved oxygen as significant correlates of gastropod assemblage structure. Gastropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Total drainage area is also an important predictor of species richness in other studies of snails in streams and lakes (Dillon and Benfi eld 1982, Jokinen 1987, Prezant and Chapman 2004 and in freshwater mussels (Ortmann 1920, Strayer 1983. We found headwaters dominated by pulmonate species, and larger streams dominated by pleurocerids and vivi parids, as reported in the literature (Brown et al 1998, Minton et al 2008, Pyron et al 2009). Barnese et al (1990) documented resource partitioning between pulmonate and prosobranch snails, while Johnson and Brown (1997) found that current regime and light penetration were important in Elimia semicarinata (Say, 1829).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Total drainage area is also an important predictor of species richness in other studies of snails in streams and lakes (Dillon and Benfi eld 1982, Jokinen 1987, Prezant and Chapman 2004 and in freshwater mussels (Ortmann 1920, Strayer 1983. We found headwaters dominated by pulmonate species, and larger streams dominated by pleurocerids and vivi parids, as reported in the literature (Brown et al 1998, Minton et al 2008, Pyron et al 2009). Barnese et al (1990) documented resource partitioning between pulmonate and prosobranch snails, while Johnson and Brown (1997) found that current regime and light penetration were important in Elimia semicarinata (Say, 1829).…”
Section: Discussionsupporting
confidence: 83%
“…Pyron et al (2009) determined that most species were found at sites with pH values ranging from 7.8 to 8. Temperature, a variable we expected to be important in infl uencing species richness, was not signifi cant.…”
Section: Discussionmentioning
confidence: 99%